Trace element analysis of high-purity graphite following open-focused microwave assisted digestion - Liu, Jianhua; Sturgeon, Ralph (Ciencia)
Microwave assisted wet digestion of high-purity graphite was successfully accomplished at atmospheric pressure using an open-focused system. Samples of 0.2 -3 g mass were treated with a 1:2 (Ê‹/Ê‹) mixture of HNO3 and H2SO4. Measurements of the residual organic carbon in the digests, trace element recovery and extent of contamination (magnitude of the blank) were used to characterize the performance of the methodology. A Prolabo Microdigest M 401 unit, fitted with a modified reaction vessel, served to digest sarnples. Trace element determinations of the graphite were completed by graphite furnace atomic absorption spectrometry (GFAAS). Accuracy was assessed via the concurrent digestion and analysis of two certified reference materias (LUTS-1, a lobster hepatopancreas from the National Research Council of Canada; and CRM 1632a, a reference coal material from the National Institute of Standards and Technology). Spike recovery of elements added to graphite samples (As. Cd, Cr, Co, Cu. Fe, Pb, Mn, Ni, Se, Sr, and Zn) averaged 88% [range 79(Pb) - 94(Cd) %]. Limits of detection (ng/g) in the graphite ranged from 0.8 (Cd) to 160 (Se). Precision of replicate determination averaged 10% (relative standard deviation) for trace impurity concentrations (ng/g) of < 2 (Pb) - 190 (As).